Influência de diferentes práticas de uso da terra sobre a fauna de riachos amazônicos - SOUSA, Híngara Leão (Universidade Federal do Pará, 2019)
Disturbances caused by land use practices lead to several negative effects on stream biodiversity. This dissertation was developed to contribute with information about the land use effects on Amazonian stream biodiversity. The dissertation was subdivided in three chapters. First, it was performed a review of articles that evaluated the land use effects on stream fauna in the Amazon in the last 25 years to show the scenario of scientific research for these ecosystems in the region. In the Chapter 2 the aim was to assess the effects of three land use practices (managed and convenctional logging, and pasture) on stream fish, considering the impacts on the community structure and niche characteristics of species. In the Chapter 3 the aim was to evaluate the ecological uniqueness of fish assemblages in these areas, in order to identify the land uses and species that more contribute to beta diversity in the region. As general results of the first Chapter, 42 articles evaluating the land use effects on stream fauna communities in the Amazon were found in the literature, mainly in areas of timber extraction. Recently, there has been an increase in studies, and only the last four years accounted for 74% of articles. However, we identified a lack of information about the land use history in the studied areas, a lack of studies using only the crustacean as a bioindicator taxon and a few multi-taxon studies. Chapter 2 showed that conventional logging and pasture had negative impacts on fish communities, and no effect was observed in managed logging areas. Additionally, pasture was mainly responsible for the separation of niche species, supporting species with higher marginality and smaller niche breadth. Finally, in the Chapter 3 was found higher contribution of pasture area to beta diversity, mainly due to the great variation in the disturbance levels associated to this land use practice. Besides that, both habitat specialist and generalists contributed to beta diversity in the area. In conclusion, the results of this dissertation have shown that different kinds of land use may result in particular effects on stream communities. Our findings also suggest that different approaches using information on stream biodiversity are useful in environmental impact assessment in these ecosystems.